Faktor – Faktor Yang Mempengaruhi Pertumbuhan Aset Bank Syariah Di Indonesia Tahun 2006-2015 - Diamantin Rohadatul Aisy; Imron Mawardi (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
This research aimed to determine the external and internal factors affect to the assets growth of Islamic banking in Indonesia, in time year 2006 until year 2015. The approach is a quantitative approach using PLS (Partial Least Square) analytical techniques with three latent variables, that is external factors as an exogenous variable wich which used to reflect external factors in this research are inflation, GDP Growth, BI rate, and money supply (M2); internal factors as an endogenous variable which are reflected by profit sharing rate, promotion, education and training cost, NPF ratio, ROA ratio, FDR ratio, Third-Party Funds, quantity of office bank, and office channeling; and assets growth of Islamic banking as an endogenous variable. The result of this research showed that external factors has a significant effect to internal factors. However, both external factors and internal factors have no significant effect to the growth of Islamic banking asset.